UJI EFEKTIVITAS Echinacea purpurea (Radix) SEBAGAI IMUNOMODULATOR TERHADAP TITER ANTIBODI AVIAN INFLUENZA (AI) DAN NEWCASTLE DISEASE (ND) PADA BROILER JANTAN - Lusia Komala Widiastuti; Purnama Edy Santosa; Siswanto Siswanto; Madi Hartono (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
This study intended to know the effectiveness of E. purpurea as an immunomodulator against AI and ND antibody titer in male broilers, and conducted in December 2018 until January 2019 at Lapang Terpadu Laboratory, Faculty of Agriculture, University of Lampung. Antibody titer analysis was done in Virology Laboratory of Balai Veteriner Lampung. The study was conducted on 60 samples of Lohmann male broiler with four treatments, P0 (drinking water without E. purpurea), P1 (drinking water with 3 mg/kg BW/day E. purpurea), P2 (drinking water with 6 mg/kg BW/day E. purpurea), and P3 (drinking water with 9 mg/kg BW/day E. purpurea). The results showed that E. purpurea (Radix) was effective to increase Avian Influenza antibody titers and was not effective to increase Newcastle Disease antibody titers in male broilers. E. purpurea (Radix) at a dose of 6 mg/kg BW/day can increase AI antibody titer in male broilers. Keywords: E. purpurea, Immunomodulator, Antibody titer, Avian Influenza, Newcastle Disease